2015
DOI: 10.1111/jgh.12801
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variant in 8q24 is associated with prognosis for gastric cancer in a Chinese population

Abstract: These findings suggested the SNP rs10505477 may contribute to the survival of gastric cancer and be a potential prognostic biomarker of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 42 publications
0
42
1
Order By: Relevance
“…Additional data support this interaction, for example, Ahmadiyeh et al (2010) suggested that enhancer elements at 8q24 form a longrange chromatin loop with MYC in a tissue-specific manner, while Kim et al (2014) found that the MYC enhancer region physically interacts with the active regulatory region of the long noncoding RNAs CARLo-5 promoter, thus regulating CARLo-5 expression, which is significantly correlated with the rs6983267 allele and increased cancer susceptibility. The association between variants on chromosome 8q24 and gastric cancer has been analyzed in recent reports Wokołorczyk et al, 2008;Guo et al, 2011;Lochhead et al, 2011;Tarleton et al, 2014;Ma et al, 2015). In this regard, Guo et al (2011) found that the GT genotype of rs6983267 was associated with an increased risk of gastric cancer compared with GG genotype in Chinese population.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Additional data support this interaction, for example, Ahmadiyeh et al (2010) suggested that enhancer elements at 8q24 form a longrange chromatin loop with MYC in a tissue-specific manner, while Kim et al (2014) found that the MYC enhancer region physically interacts with the active regulatory region of the long noncoding RNAs CARLo-5 promoter, thus regulating CARLo-5 expression, which is significantly correlated with the rs6983267 allele and increased cancer susceptibility. The association between variants on chromosome 8q24 and gastric cancer has been analyzed in recent reports Wokołorczyk et al, 2008;Guo et al, 2011;Lochhead et al, 2011;Tarleton et al, 2014;Ma et al, 2015). In this regard, Guo et al (2011) found that the GT genotype of rs6983267 was associated with an increased risk of gastric cancer compared with GG genotype in Chinese population.…”
Section: Discussionmentioning
confidence: 95%
“…Particularly, the 8q24 chromosome region has been suspected to contain several cancer risk variants that lead to numerous cancer types, including breast, prostate, thyroid, colorectal and gastric cancer (Easton et al, 2007;Berndt et al, 2008;Ghoussaini et al, 2008;Wokołorczyk et al, 2008Wokołorczyk et al, , 2009Yeager et al, 2009;Turnbull et al, 2010;Von Holst et al, 2010;Guo et al, 2011;Lochhead et al, 2011;Neta et al, 2012;Ma et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This SNP also maps to the intron of a long noncoding RNA (lncRNA), cancer-associated region long noncoding RNAs-1 ( CARLos-1 ). Silico studies have shown that rs10505477 change the CARLos-1 local folding structure, which suggests it may lead to aberrant expression of CARLos-1 [37]. Although the biological function of CARLos-1 is still unclear, the CARLos-5 , which is in the same region with CARLos-1 , has a function in tumor development [38], indicating that CARLos-1 may also play a role in carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) and several case–control studies have proved that some particular variants in CASC8 had correlation with carcinomas such as breast cancer, colorectal cancer (CRC), prostate cancer (pCa), upper gastrointestinal cancer, lung cancer, and gastric cancer 610. The single-nucleotide polymorphism (SNP) of rs10505477 – located in the intron of the lncRNA of CASC8 gene – had an intimate correlation with CRC susceptibility,1113 the risk of lung cancer, the prognosis for gastric cancer,14,6 and so on. Rs7837328 – another polymorphism in CASC8 – was associated with pCa and CRC susceptibility 7,15.…”
Section: Introductionmentioning
confidence: 99%